Ammonia-based compression heat pumps for simultaneous heating and cooling applications in milk pasteurization processes: Performance evaluation. (25th November 2022) - Ayou, Dereje S.; Hargiyanto, Reza; Coronas, Alberto
Highlights: Investigation of ammonia-based heat pumps use in the milk pasteurization process. Exergy efficiency of NH3 and NH3 /H2 O heat pumps are 58% and 44–50% at 73 K lift. Primary energy savings by NH3 and NH3 /H2 O heat pumps are 54% and 41–47% at 73 K lift. NH3 /H2 O heat pump operates at much lower system high-pressure than NH3 heat pump. Abstract: Ammonia-based heat pumps were investigated to deliver heating (65–95 °C) and cooling (2 °C) simultaneously for the pasteurization of raw milk. Two compression heat pump configurations using a pure refrigerant (ammonia) and zeotropic mixture (ammonia/water) as working fluids were integrated with raw milk pasteurization process: two-stage ammonia compression heat pump with closed intercooler, and two-stage ammonia/water compression heat pump with a solution circuit. The integrated heat pump systems performance simulations were carried out at the base-case design conditions and parametric study on the influence of key operational variables on the system's first- and second-law efficiencies. These heat pumps are attractive and more efficient solutions than current heating and cooling systems used in the dairy processing industries (fossil-fuel-fired boiler and ammonia compression chiller) by up to 59% of a primary energy saving. Besides, the two-stage ammonia/water heat pump operates at a lower system high pressure than the ammonia heat pump, which allows reducing the cost of the system components, especially for the compressor. The development of such types of multi-stage compression heat pumps (with large-temperature-lift) using zeotropic mixture with wide temperature glide, as a working fluid, significantly contributes towards the decarbonization of the dairy processing industry.